2020
DOI: 10.21059/buletinpeternak.v44i1.42311
|View full text |Cite
|
Sign up to set email alerts
|

Total Count of Lactic Acid Bacteria in Goats and Cows Milk Yoghurt using Starter S. thermophilus RRAM-01, L. bulgaricus RRAM-01 and L. acidophilus IIA-2B4

Abstract: Yoghurt is a well-known fermented dairy product which produced using a combination of lactic acid bacteria (LAB) of Streptococcus thermophilus, Lactobacillus bulgaricus and L. acidophillus as fermentation starters. Cow milk is usually used as a raw ingredient. The LAB-based local yoghurt starter (S. thermophilus RRAM-01 (ST), L. bulgaricus RRAM-01 (LB) and L. acidophilus IIA-2B4 (LA)) were previously isolated from milk and meat, nevertheless had not been extensively attempted to be used in yoghurt production. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…Treatment E (threonine 3g/L) was the highest treatment in S. thermophilus and Lb. bulgaricus count because threonine good nutrient that promoted the growth and activity of yogurt starter bacteria, threonine is one of the most important sources of nitrogen stimulating growth and reproduction, while it was the lowest value for (B) glycine 1g/L, the reason for this may be attributed to the fact that some strains of S. thermophilus have weak growth in the presence of glycine, these results are in agreement with (Tamime and Robinson, 2007;Mega et al, 2019).…”
Section: Yogurt Starter Bacteriasupporting
confidence: 83%
“…Treatment E (threonine 3g/L) was the highest treatment in S. thermophilus and Lb. bulgaricus count because threonine good nutrient that promoted the growth and activity of yogurt starter bacteria, threonine is one of the most important sources of nitrogen stimulating growth and reproduction, while it was the lowest value for (B) glycine 1g/L, the reason for this may be attributed to the fact that some strains of S. thermophilus have weak growth in the presence of glycine, these results are in agreement with (Tamime and Robinson, 2007;Mega et al, 2019).…”
Section: Yogurt Starter Bacteriasupporting
confidence: 83%
“…LcS population density was determined using the standard plate count (SPC) method on de Man, Rogosa, and Sharpe (MRS) agar, expressed in colony-forming units (CFU)/g (Agustine et al, 2018). Lactic acid concentration was determined using the total titrated acid method, and pH was recorded using a digital pH-meter (Mega et al, 2020). Graphical images were generated using GraphPad Prism ver.…”
Section: Methodsmentioning
confidence: 99%
“…bulgaricus and Streptococcus thermophilus. Mega et al (2020) previously reported that using additional probiotics such as Lactiplantibacillus plantarum or Lactobacillus acidophilus resulted not only in a yogurt with better characteristics but also in a higher probiotic content. Arief et al (2015) had previously isolated local probiotics of L. plantarum IIA-1A5 and L. acidophilus IIA-2B4, which were shown to be good probiotic supplements for yogurt.…”
Section: Introductionmentioning
confidence: 99%